Education Nutrition, Pattern Foster Care And Giving Food Additional Toddlers Prevent Stunting In Hall Ii, Wonokerto Village, Tugumulyo District, Musi Rawas Regency - Ema Martini; Fauziah, Fauziah; Kardila , Lesi; Yuliani , Syami; Sari , Fikitri Marya (Jurnal Inovasi Kerja Nyata, 2025)
. Stunting is a serious public health problem, characterized by a condition of failure to thrive in toddlers due to chronic malnutrition, especially in the first 1,000 days of life. The impact is not only on physical growth, but also cognitive development and productivity in the future. Based on data, the prevalence of stunting in Musi Rawas Regency is still quite high, at 15.3%. In Wonokerto Village, 6 out of 38 toddlers (15.8%) were found to experience stunting, indicating the need for interventions based on education and community empowerment. This activity aims to increase awareness and knowledge of parents of toddlers regarding the importance of balanced nutrition, good parenting patterns, and the provision of nutritious supplementary foods (PMT) based on local food ingredients. The methods used include nutrition and parenting counseling, demonstrations of making PMT, and monitoring toddler growth. The results of the implementation showed an increase in knowledge of mothers of toddlers, changes in behavior in feeding children, and active community involvement in PMT activities. Education integrated with direct practice has proven effective in building community awareness and participation. This activity is expected to support government programs in accelerating the reduction of stunting at the village level in a sustainable manner.